Emperor of Japan : Meiji and his world, 1852-1912 - Keene, Donald (New York : Columbia University Press, 2002)
Review: When Emperor Meiji began his rule in 1867, Japan was a splintered empire, dominated by the shogun and the daimyos, who ruled over the country's more than 250 decentralized domains and who were, in the main, cut off from the outside world, staunchly anti-foreign, and committed to the traditions of the past. Before long, the shogun surrendered to the emperor, a new constitution was adopted, and Japan emerged as a modern, industrialized state. Despite the length of his reign, little has been written about the strangely obscured figure of Meiji himself, the first emperor ever to meet a European. Most historians discuss the period that takes his name while barely mentioning the man, assuming that he had no real involvement with the affairs of the state. Even Japanese who believe Meiji to have been their nation's greatest ruler may have trouble recalling a single personal accomplishment that might account for such a glorious reputation. Donald Keene sifts the available evidence to present a portrait not only of Meiji but also of rapid and sometimes violent change during this pivotal period in Japan's history. We move with the emperor through his early, traditional education; join in the formal processions that acquainted the young emperor with his country and its people; observe his behavior in court, his marriage, and his relationships with various consorts; and follow his maturation into a "Confucian" sovereign dedicated to simplicity, frugality, and hard work. Later, during Japan's wars with China and Russia, we witness Meiji's struggle to reconcile his personal commitment to peace and his nation's increasingly militarized experience of modernization.
Keywords: Emperors -- Biography. -- Japan; Meiji, Emperor of Japan 1952-1912; Industrialization -- History. -- Japan; Japan -- History -- Meiji period, 1868-1912.